Role of Ngos In Upliftment of Rural Rajasthan (With Special Emphasis on Education): Examining the Impact of NGOs on Education and Empowerment in Rural Rajasthan (Journal of Advances and Scholarly Researches in Allied Education, 2012)
In the present study, data relating to60 NGOs working in different district in Rajasthan were collected. The 60 NGOswere selected randomly from 33 district of Rajasthan. NGO in the rural areaswere mainly devoted to environment, women upliftment, health but most of themare educational institution. Many NGOs such as Bodh, Diganter, Kalp, SevaMandir, Pratham Pahal, Ajim Prem G Foundation, Dushra Dashak, and Jksms are nodoubt working very well in Rajasthan. BGVS (bharat gyan vigyan samiti) mainly deals in right to educatecampaign (RTE). NGOs like Bodh and Diganter deals in higher secondary educationin rural areas of Rajasthan especially in Jaipur district.  Now they are training government schoolteachers about how to deal with children coming from schools of NGOs.